2014
DOI: 10.1371/journal.pone.0086327
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Low-Cost Bubble CPAP System in Treatment of Respiratory Distress in a Neonatal Ward in Malawi

Abstract: BackgroundRespiratory failure is a leading cause of neonatal mortality in the developing world. Bubble continuous positive airway pressure (bCPAP) is a safe, effective intervention for infants with respiratory distress and is widely used in developed countries. Because of its high cost, bCPAP is not widely utilized in low-resource settings. We evaluated the performance of a new bCPAP system to treat severe respiratory distress in a low resource setting, comparing it to nasal oxygen therapy, the current standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
158
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(167 citation statements)
references
References 24 publications
5
158
3
1
Order By: Relevance
“…18 The use of CPAP is effective for the treatment of respiratory failure in high-income countries, [5][6][7] but there are few reports of the use of CPAP in low-income settings. [10][11][12]19 Bubble CPAP is an attractive device for treating neonates with respiratory distress due to its simple design, low cost, and potential to improve survival rates in settings lacking mechanical ventilation. However, in an effort to provide bubble CPAP to neonates with respiratory distress in low-income and middle-income countries, health-care providers may use untested homemade devices despite uncertainty about the devices' ability to deliver CPAP reliably.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The use of CPAP is effective for the treatment of respiratory failure in high-income countries, [5][6][7] but there are few reports of the use of CPAP in low-income settings. [10][11][12]19 Bubble CPAP is an attractive device for treating neonates with respiratory distress due to its simple design, low cost, and potential to improve survival rates in settings lacking mechanical ventilation. However, in an effort to provide bubble CPAP to neonates with respiratory distress in low-income and middle-income countries, health-care providers may use untested homemade devices despite uncertainty about the devices' ability to deliver CPAP reliably.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12]21 In a study from South Africa, Pieper et al 21 reported the use of nasal CPAP in 11 extremely lowbirthweight infants with respiratory distress following birth compared with 10 control infants. Infants treated with nasal CPAP had a mean birthweight of 915 g and a mean gestational age of 28.6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las acciones dirigidas a mejorar la sobrevida sin secuelas neurológicas en el prematuro menor de 1.500 gramos tendrían un impacto favorable en la salud pública (13) .…”
Section: Introductionunclassified
“…The benefits have included improved survival, 15 a reduction in the adverse events related to endotracheal intubation, reductions in ICU and hospital stay, and significantly reduced costs to health-care systems and to patients, 16 and in some parts of the world, this technology has provided access to ventilatory support that was simply not available before. 17 In settings such as status asthmaticus, there is a suggestion that some modes of NIV relieve symptoms but may also reduce airway reactivity. 18 However, there remains a paucity of randomized, controlled studies to fully evaluate the impact of NIV, particularly in children.…”
mentioning
confidence: 99%